Procedure For Managing The Ship Operation Plan In The Simlala System To Support Ship Operational Activities At The Port Of Pt. Usda Seroja Jaya Batam - Naomi Monalisa Sitompul; Dina Rispianti (KALAO'S MARITIME JOURNAL, 2024)
PT. Usda Seroja Jaya is a company engaged in the fields of Shipping, Shipyard, and Agency. During the process of a ship's arrival at Batam port, it is necessary to manage the Ship Operation Plan (RPK). The Ship Operation Plan (RPK) is a document that serves as proof of the placement of an Indonesian-flagged vessel at a port to support domestic sea transportation activities. There are two types of shipping routes in the Ship Operation Plan (RPK): Regular and Scheduled Routes (Liner), which refer to scheduled and regular sea transport services with specified stopover ports, and Irregular and Unscheduled Routes (Tramper), which refer to sea transport services that are not fixed or scheduled.In this paper, the author uses field research, observation, and library research methods to address the handling of the Ship Operation Plan (RPK) within the SIMLALA system. Common challenges include unstable internet connections, which hinder the processing of the RPK, frequent server errors or troubles within SIMLALA, and large file sizes. Therefore, it is crucial to ensure timely processing of the RPK in SIMLALA. The purpose of this study is to understand the process of managing the RPK within SIMLALA so that ship operations are not disrupted. In conclusion, the management of the Ship Operation Plan (RPK) at PT. Usda Seroja Jaya must be carried out properly to ensure that the RPK process runs smoothly.